The Influence of Work Discipline and Workload on Employee Performance: Study At One of The Banks in Bandung - Oktaviani, Nindi Dwi; Satria, Rd. Okky; Adinata, Ujang Wawan Sam; Sukmalana, Soelaiman; Supartini, Tini; Titi, Titi (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
This study was done by selecting a sample of 40 respondents from the population. This study investigates the use of SPSS 22 software for Windows operating systems. The research findings are as follows: A study was conducted to assess the work discipline of employees at a bank in Bandung. The data processing revealed that the average rating of respondents' responses was 2.98, which falls within the